Avaliação da suportabilidade de estruturas monofásicas de redes de distribuição aéreas compactas frente a impulsos atmosféricos normalizados - Guilherme da Silva Lima (2015)
This work is dedicated to investigate the impulse withstand voltage of single-phase compact distribution line structures when subjected to standard lightning impulse waveforms with positive and negative polarities. It is also dedicated to estimate parameters to characterize such withstand. Three situations were considered in laboratory tests with the evaluated structures, which are the ones most frequently used in the state of Minas Gerais, Brazil: (i) covered cables with new insulation; (ii) covered cables with punctured insulation after application of standard lightning impulses; (iii) bare cables, aiming at assessing the critical case in which the insulating cover is completely deteriorated. The results show that the application of standard lightning impulses with positive polarity on structures with bare cables leads to critical flashover overvoltages (U50) with values between 129.9 kV and 185.4 kV. For the application of standard lightning impulses with negative polarity, U50 assumed values between 155.9 kV and 204.5 kV. In all cases using bare cables, parameters of the Uxt curves corresponding to the evaluated structures were estimated. Parameters for the disruptive effect method (DE method), which allows estimating the response of the evaluated structures when subjected to non-standard voltage waveforms, were also determined. In assessing the voltage withstand of compact distribution line structures considering cables with brand new insulating cover, mean breakdown voltages between 197.3 kV and 289.7 kV were obtained for the application of impulse voltages with positive polarity, while values between 219.5 kV and 243.8 kV were obtained for impulse voltages with negative polarity. The results therefore demonstrate that the insulating cover of the cables contributes to an increase in the voltage withstand of compact distribution line structures when subjected to lightning impulse waveforms. Furthermore, it was observed that the distance between a pinhole on the cable cover to the nearest grounded point can affect the withstand level of the structure. Pinholes close to the structure reduce the voltage withstand to levels that approach the critical case where the covered cable is replaced by a bare cable. On the other hand, pinholes far away from the structure lead the withstand level to approach the condition of a new cable, depending on the polarity of the applied impulse voltage.